2010
DOI: 10.1371/journal.pone.0010659
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease Amyloid-β Links Lens and Brain Pathology in Down Syndrome

Abstract: Down syndrome (DS, trisomy 21) is the most common chromosomal disorder and the leading genetic cause of intellectual disability in humans. In DS, triplication of chromosome 21 invariably includes the APP gene (21q21) encoding the Alzheimer's disease (AD) amyloid precursor protein (APP). Triplication of the APP gene accelerates APP expression leading to cerebral accumulation of APP-derived amyloid-β peptides (Aβ), early-onset AD neuropathology, and age-dependent cognitive sequelae. The DS phenotype complex also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
114
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 41 publications
14
114
0
1
Order By: Relevance
“…This figure is higher than that of the general population, where the reported prevalence of cataract was 35% for those 40 years or older among Chinese in Singapore (The Tanjong Pagar Survey) 16. Susceptibility to oxidative stress17 and the expression and accumulation of amyloid precursor protein and amyloid-β peptides 18 19 in the lens have been proposed as mechanisms for the pathogenesis of early onset cataract in DS patients. As cataract surgery is becoming safer and more efficient, screening and early treatment for visually significant cataracts may be beneficial in this population.…”
Section: Discussionmentioning
confidence: 90%
“…This figure is higher than that of the general population, where the reported prevalence of cataract was 35% for those 40 years or older among Chinese in Singapore (The Tanjong Pagar Survey) 16. Susceptibility to oxidative stress17 and the expression and accumulation of amyloid precursor protein and amyloid-β peptides 18 19 in the lens have been proposed as mechanisms for the pathogenesis of early onset cataract in DS patients. As cataract surgery is becoming safer and more efficient, screening and early treatment for visually significant cataracts may be beneficial in this population.…”
Section: Discussionmentioning
confidence: 90%
“…In the most recent study, evaluation of DS lenses revealed a characteristic pattern of supranuclear opacification accompanied by accelerated supranuclear Aβ accumulation, co-localizing amyloidal pathology, and fiber cell cytoplasmic Aβ aggregates (~5-50 nm) identical to the lens pathology identified in Alzheimer's disease. 23 Considering the high prevalence of myopia in the age group over 20 years we propose the clinical guidelines for young adults with DS to be modified. Instead of every 5 years, 24 we recommend ophthalmologic and refractive screening every second year after 6 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Observed opacities were quantified using the Lens Opacities Classification System, version II (18 -20). For ex vivo phenotyping, eyes were dissected for lens phenotyping by ex vivo dark field photomicroscopy as described previously (21,22). For measurement of glucose levels, mice were fasted for 8 h. Glucose was measured in blood from the tail vein using the Elite system (Bayer) glucometer as described by the manufacturer.…”
Section: Analysis Of Sep15 Expression In the Lens During Embryonicmentioning
confidence: 99%